Valganciclovir for Symptomatic Congenital Cytomegalovirus Disease. Issue 8 (August 2015) - Kimberlin, David W.; Jester, Penelope M.; Sánchez, Pablo J.; Ahmed, Amina; Arav-Boger, Ravit; Michaels, Marian G.; Ashouri, Negar; Englund, Janet A.; Estrada, Benjamin; Jacobs, Richard F.; Romero, José R.; Sood, Sunil K.; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Congenital cytomegalovirus (CMV) affects 0.6% to 0.7% of live births in industrialized nations. It is the leading viral cause of mental retardation and can also result in sensorineural hearing loss. Accepted treatment for patients with symptomatic congenital CMV involving the central nervous system includes intravenous ganciclovir, but the benefits of intravenous ganciclovir may wane over time. Oral therapy with valganciclovir has also been used in the treatment of congenital CMV, and the benefit of longer therapy was studied in this randomized controlled trial. A total of 40 sites participated in the study, and newborns were eligible if they had symptomatic congenital CMV disease, without or without central nervous system involvement. All patients received valganciclovir for 6 weeks, and 1 group continued the treatment for 4.5 months, whereas the rest received a placebo. Change in hearing in the better ear was measured as the primary end point. From 31 study sites, a total of 96 participants were randomized, with 47 participants receiving 6 months of treatment and 49 receiving placebo. A total of 12 stopped taking the blinded medication before the end of the study, but none did so because of adverse events. At 6 months, hearing in the better ear was similar between the 2 groups, with 2 having improvement in the 6-month group and 3 having improvement in the 6-week group, and 5 and 3, respectively, worsening (P = 0.41). At 12 months, total-ear hearing was more likely to be improved or remain normal in patients in the 6-month group than in the 6-week group (73% vs 57%, P = 0.001). The 6-month group scored better on the Bayley Scales of Infant and Toddler Development than did the 6-week group after 24 months on the receptive-communication scale (P = 0.003) and the language-composite scale (P = 0.004). Grade 3 or 4 neutropenia was not different in the 6-month versus the 6-week group (21% vs 27% after 6 months, P = 0.64). These findings suggest 6 months, compared with 6 weeks, of oral valganciclovir among infants with symptomatic congenital CMV disease modestly improved hearing, not in the short term, but in the long term. The prolonged treatment also appeared to improve developmental outcomes modestly.